Long-term development of Kenya's growth potential. Issue 5 (3rd September 2021) - Oberholzer, Basil
ABSTRACT: This analysis of balance-of-payments-constrained growth according to Thirlwall's law shows that Kenya's growth has been balance-of-payments-constrained in the long term. The basic version of the law does not fit the data since actual growth was above the rate suggested by a balanced trade account. However, the extended version is confirmed because of a partial improvement of Kenya's terms of trade and capital inflows resulting in the accumulation of foreign debt allowed for a higher growth rate. By endogenously identifying structural breaks in Kenya's growth history and testing Thirlwall's law for the respective subperiods, an increase of the growth potential since the 1980s is observed. However, this development went along with a shift in economic activity from agriculture and manufacturing to services and construction while the informal sector multiplied in size. The results thus suggest that the external constraint was not relaxed by the development of productive capacity but by stagnating or even falling incomes and precarization in the labor market, which restricted imports. Therefore, the surge in growth since the beginning of the 21 st century has involved an increasing trade deficit and growing external debt.